2007
DOI: 10.1038/sj.npp.1301317
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Dependence, Symptoms and Oxidative Stress in Male Patients with Schizophrenia

Abstract: The high rate of smoking in schizophrenia may reflect patients' attempts to reduce the side effects of antipsychotic medications, and one mechanism for this reduction may be a reduction in oxidative stress and free radical-mediated brain damage that may contribute to schizophrenic symptoms and to complications of its treatment. Symptoms were assessed with the Positive and Negative Syndrome Scale (PANSS), side effects were assessed with the Simpson and Angus Rating Scale (SAS), and malondialdehyde (MDA), supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 40 publications
2
24
1
1
Order By: Relevance
“…Also, it has been shown that the level of lipid peroxidation increases in smokers [43]. Nicotine, on the other hand, in low, acute doses could act as an antioxidant [33]. In our study, rats exposed to 0.3 mg/kg amounts of nicotine for 7 continuous days had decreased activities of SOD and GPX and increased MDA and ROS levels following this nicotine treatment regime.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Also, it has been shown that the level of lipid peroxidation increases in smokers [43]. Nicotine, on the other hand, in low, acute doses could act as an antioxidant [33]. In our study, rats exposed to 0.3 mg/kg amounts of nicotine for 7 continuous days had decreased activities of SOD and GPX and increased MDA and ROS levels following this nicotine treatment regime.…”
Section: Discussionsupporting
confidence: 49%
“…Significantly higher liver and serum levels of MDA, conjugated dienes, hydroperoxides, and free fatty acids have all been induced in rats by exposure to cigarette smoke [29,30]. Also, nicotine treatment significantly decreased the endogenous antioxidant status in, for example, superoxide dismutase (SOD) and glutathione peroxidase (GPX) activities [31][32][33]. A decrease in the activities of these free radical scavenging enzymes could result in generation of superoxide anions and hydrogen peroxide which in turn produce hydroxyl free radicals, the cause of many toxic reactions [34].…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to differences in GSH consumption and de novo synthesis based on oxidative stress states (Dringen, 2000;Dringen and Hirrlinger, 2003). Whereby higher levels of alcohol and/or tobacco consumption promote the production of ROS (Nordmann et al, 1990;Zhong et al, 2012;Zhang et al, 2007), leading to higher GSH consumption (Janaky et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, ethanol and cigarette smoke have a demonstrated propensity to stimulate the formation of reactive oxygen species (ROS) resulting in oxidative stress (Li and Wang, 2004, Mendez-Alvarez et al, 1998, Nordmann et al, 1990, Zhang et al, 2007. Neural tissue is especially prone to such stress due to its high consumption of oxygen and resultant production of ROS, easily oxidisable substrates such as lipids with unsaturated fatty acids and relatively low activity of antioxidant defence molecules (Halliwell, 1992;Dringen, 2000;Halliwell, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco use has previously been found to exacerbate deficits noted in other neurometabolites investigated in alcohol 1 H-MRS studies (Meyerhoff et al, 2013). Due to the high comorbidity between drinking and smoking, the individual effects of alcohol and tobacco are unlikely to be reconciled using available technologies, but given they are both associated with worse illness outcomes in BD (Berk et al, 2008c;Goldstein et al, 2008) and production of ROS (Li and Wang, 2004;Zhang et al, 2007), a reasonable interpretation is that comorbid alcohol and tobacco use exhibit a greater, combined oxidative effect. It is unclear whether the compounded neurobiological effect of the alcohol-tobacco comorbidity is associated with a greater impact on neuroprogression of BD nonetheless it would be logical to speculate that it does.…”
Section: Glutathione Bipolar Disorder and Alcoholmentioning
confidence: 99%